IGF-1 impacts neocortical interneuron connectivity in epileptic spasm generation and resolution - Carlos J. Ballester-Rosado; John T. Le; Trang T. Lam; Anne E. Anderson; James D. Frost, Jr.; John W. Swann (Neurotherapeutics)
Little is known about the mechanisms that generate epileptic spasms following perinatal brain injury. Recent studies have implicated reduced levels of Insulin-like Growth Factor 1 (IGF-1) in these patients’ brains. Other studies have reported low levels of the inhibitory neurotransmitter, GABA. In the TTX brain injury model of epileptic spasms, we undertook experiments to evaluate the impact of IGF-1 deficiencies on neocortical interneurons and their role in spasms. Quantitative immunohistochemical analyses revealed that neocortical interneurons that express glutamic acid decarboxylase, parvalbumin, or synaptotagmin 2 co-express IGF-1. In epileptic rats, expression of these three interneuron markers were reduced in the neocortex. IGF-1 expression was also reduced, but surprisingly this loss was confined to interneurons. Interneuron connectivity was reduced in tandem with IGF-1 deficiencies. Similar changes were observed in surgically resected neocortex from infantile epileptic spasms syndrome (IESS) patients. To evaluate the impact of IGF-1 deficiencies on interneuron development, IGF-1R levels were reduced in the neocortex of neonatal conditional IGF-1R knock out mice by viral injections. Four weeks later, this experimental maneuver resulted in similar reductions in interneuron connectivity. Treatment with the IGF-1 derived tripeptide, (1–3)IGF-1, abolished epileptic spasms in most animals, rescued interneuron connectivity, and restored neocortical levels of IGF-1. Our results implicate interneuron IGF-1 deficiencies, possibly impaired autocrine IGF-1 signaling and a resultant interneuron dysmaturation in epileptic spasm generation. By restoring IGF-1 levels, (1–3)IGF-1 likely suppresses spasms by rescuing interneuron connectivity. Results point to (1–3)IGF-1 and its analogues as potential novel disease-modifying therapies for this neurodevelopmental disorder.